(untitled) (The Pakistan Development Review, 1998)
Fiscal policy, being an embodiment of government measures to raise resources through taxes, tariffs of utilities, user charges and pricing of public sector goods, diverts resources from private sector to the government which rechannels these resource into socially preferred activities. The resource diversion and their rechannelisation helps achieve certain economic goals, and for this reason, the fiscal policy has strong interactive linkages with other macro economic policies. By virtue of this strong bond, the fiscal indicators have a close interactive association with other macro economic indicators. For this reason, the role of fiscal policy is inevitably vulnerable to influences of other economic policies and fiscal discipline and general economic health of the country become interlinked. This linkage results in generating trade offs between different macroeconomic policy goals.